Proposta de critérios de sustentabilidade nas fases preliminares de projetos de business intelligence - Costa, Dyego Márcio Damasceno (2024)
Business Intelligence (BI) resources enable the collection of strategic information from large volumes of data, allowing organizations to make decisions aimed at reducing environmental impacts. The objective of this work is to propose sustainable criteria to structure the initial phases of a BI project with an emphasis on sustainable objectives. To this end, a systematic literature review was developed using the Methodi Ordinatio. Based on the bibliographic review, it was possible to identify sustainable criteria and demands for BI data analysis, such as verifying needs and improvements in data extraction, integration and standardization. As an example of application to test the criteria, a case study was developed in a precast cement factory, analyzing all processes and which types of sustainable data can be structured in the initial phases of a BI project with an emphasis on sustainability. As a result of the application of the criteria in data mapping, it was found, among others, that this application reduces the scope of data to be collected and thus facilitates the modeling of subsequent phases, also reducing the impact on the processing of computational resources. Furthermore, by defining categories and types of data, it was possible to have a comprehensive view of data with the same classification, such as waste generation in each sector, which makes it possible to generate a history of this data. As for data processing processes, the application of sustainable criteria made it possible to identify which metrics and types of data should be extracted from the databases. Therefore, it is clear that establishing well-defined sustainability criteria and indicators is essential for collecting data and preparing it for a reliable BI project.